Analysis of organizational culture dimensions impacting performance - Ginevičius, Romualdas; Vaitkūnaite, Vida (Journal of Business Economics and Management, 2006)
The paper reveals multidimensional nature of organizational culture. When investigating its influence on success only performance influencing dimensions must be under consideration. The authors suggest the ways for reducing their number: content analysis and hierarchical structuring method. The system (list) of dimensions was formed by using the mentioned methods. Questionnaire was made. Relationship between dimensions and their influence on performance was tested.Firstd Published Online: 14 Oct 2010